2018
DOI: 10.1016/j.wasman.2018.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Real-time optimization of the key filtration parameters in an AnMBR: Urban wastewater mono-digestion vs. co-digestion with domestic food waste

Abstract: Highlights  Average costs of €0.047 (UWW) and €0.067 per m 3 (UWW and FW) were obtained  Energy costs accounted for 59.6% and 69.0% of the total costs respectively  Average reversible fouling removal downtimes were 0.4% and 1.6% respectively  Control strategy efficiently minimized filtration costs for both substrates *Highlights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…In wastewater treatment especially, these processes result in increased energy intensities. Robles et al., for instance, reported that gas sparging to clean an AnMBR made up 79.7% of the AnMBR energy demand, while Harclerode et al found that pumping and gas sparging comprise 35–76% of an AnMBR’s energy consumption …”
Section: Fouling Impacts On Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…In wastewater treatment especially, these processes result in increased energy intensities. Robles et al., for instance, reported that gas sparging to clean an AnMBR made up 79.7% of the AnMBR energy demand, while Harclerode et al found that pumping and gas sparging comprise 35–76% of an AnMBR’s energy consumption …”
Section: Fouling Impacts On Operationmentioning
confidence: 99%
“…For AnMBR treatment of municipal wastewater, some claim that cleaning comprises 2–7% of OPEX . Lin and Chen et al found that the cost of chemicals to clean the AnMBR represented approximately 32.5% of OPEX, , while a different AnMBR study found the costs of cleaning chemicals to be 17% of OPEX, although it should be noted that both of these studies only evaluated costs of the AnMBR unit operation, not of an entire wastewater treatment plant (WWTP). Membrane cleaning disrupts operations and decreases efficiency and performance. , In the case of RO processes, Patil et al state that RO membrane cleaning comprised ∼33% of OPEX, while a different analysis suggests that cleaning chemical costs normally contribute about 10% to OPEX .…”
Section: Fouling Impacts On Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that it was sufficient to install two membrane modules for a medium-size operation, in a two-phase extraction mill, in order to optimize the capital costs and minimize operation and maintenance expenses. Robles, Capson-Tojo, Capson-Tojo, Ruano, Seco, and Ferrer (2018) showed that AnMBRs could be successfully applied to domestic wastewater treatment based on a quantitative economic and environmental assessment protocol they developed. Based on their analyses, the authors also noted that the AnMBR modeling may need more attention.…”
Section: Membrane Treatment Technologiesmentioning
confidence: 99%
“…Robles, Capson‐Tojo, Capson‐Tojo, Ruano, Seco, and Ferrer (2018) showed that AnMBRs could be successfully applied to domestic wastewater treatment based on a quantitative economic and environmental assessment protocol they developed. Based on their analyses, the authors also noted that the AnMBR modeling may need more attention.…”
Section: Membrane Treatment Technologiesmentioning
confidence: 99%